Etika dan Spirit Directing dalam Al-Qur’an dan Hadis: Landasan Normatif bagi Kepemimpinan Pendidikan Islam Modern - Songyanan, Afifudin; Raya, Ahmad Thib (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the concept of directing in the Qur'an and Hadith and its relevance to Islamic educational leadership practices. The method used is qualitative research with a thematic interpretation and Hadith approach (maudhu‘i), through analysis of Qur’anic verses and Hadiths related to directing, leadership, and the educational process. The data is analysed descriptively and analytically to identify the basic principles of directing from an Islamic perspective. The results of the study show that directing in Islam is carried out based on the values of trust, justice, wisdom, and deliberation, and is applied through the targhib wa tarhib pattern as a form of educational guidance. These findings confirm that the function of directing is not only oriented towards achieving organisational goals, but also towards shaping the moral and spiritual dimensions of Islamic educational leadership. Thus, the concept of directing based on the Qur'an and Hadith has an important contribution to supporting the practice of character-based and sustainable Islamic educational leadership.